Percutaneous approach to a tight post-isthmic aortic coarctation: a case report and literature review - Cortese, Francesca; Gesualdo, Michele; Acquaviva, Tommaso; Cortese, Annamaria; De Cillis, Emanuela; Ciccone, Marco M; Bortone, Alessandro Santo (Journal of Advances in Internal Medicine, 2017)
Correction: Figure 1 and Figure 2 were omitted from the PDF. On 5th June 2017, the new PDF including the figures was uploaded and the page numbers of the article changed from 41-44 TO 41-45. A 17 years-old boy with hypertension underwent cardiology assessment for episodes of dyspnoea and palpitations. Cardiac angiography showed post-istmic severe aortic coarctation. The malformation was successful treated by implanting a covered stent in aorta. The manuscript describes in detail this case and analyzes the available literature on the topic. Journal of Advances in Internal Medicine Vol.5(2) 2016: 41-45